Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1093/nar/gkt1341
|View full text |Cite
|
Sign up to set email alerts
|

An H2A histone isotype regulates estrogen receptor target genes by mediating enhancer-promoter-3′-UTR interactions in breast cancer cells

Abstract: A replication-dependent histone H2A isotype, H2ac, is upregulated in MCF-7 cells and in estrogen receptor-positive clinical breast cancer tissues. Cellular depletion of this H2A isotype leads to defective estrogen signaling, loss of cell proliferation and cell cycle arrest at G0/G1 phase. H2ac mediates regulation of estrogen receptor target genes, particularly BCL2 and c-MYC, by recruiting estrogen receptor alpha through its HAR domain and facilitating the formation of a chromatin loop between the promoter, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 45 publications
3
25
1
Order By: Relevance
“…Interestingly, the levels of H2A 1C and H2A 1B/E displayed a statistically significant increase as the cells became more tumorigenic. This observation is consistent with the recent report that increased levels of H2A 1C are seen in estrogen receptor positive breast cancers [ 16 ]. Changes in less abundant H2A species were also observed, such as the mono-methylated form of H2A 1H which decreased in abundance as the breast cancer cells became more malignant (Table 2 ).…”
Section: Resultssupporting
confidence: 94%
“…Interestingly, the levels of H2A 1C and H2A 1B/E displayed a statistically significant increase as the cells became more tumorigenic. This observation is consistent with the recent report that increased levels of H2A 1C are seen in estrogen receptor positive breast cancers [ 16 ]. Changes in less abundant H2A species were also observed, such as the mono-methylated form of H2A 1H which decreased in abundance as the breast cancer cells became more malignant (Table 2 ).…”
Section: Resultssupporting
confidence: 94%
“…Differential expression of H2B1B had not been identified before, but low-H2B1M expression was identified as a biomarker for breast cancer and gastric cancer progression in microarray and proteomics studies [ 42 , 43 ]. Previous investigations of canonical H2A isoforms found that up-regulation of specific H2A sequences in chronic lymphocytic leukemia and in MCF-7 breast cancer cells caused increased proliferation and carcinogenesis in those cell types [ 44 , 45 ]. Similar studies should be performed by overexpressing H2B1B and H2B1M in some of the cancer cells where the levels of these variants are very low to see if this causes a decrease in cancer cell proliferation or progression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, over-expression of a truncated ERα, lacking the DNA-binding domain (ERα 264–595 ) [24], decreased the induction of IL-20 expression in E2-induced MCF-7 cells (Fig 2B). As expected, both over-expression of ERα 264–595 and treatment with ICI inhibited the recruitment of RNA Pol II to IL-20 chromatin (Fig 2E).…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic assembly and dissolution of co-regulators from estrogen responsive promoters following E2-liganded ERα activation and deactivation turns the basal transcription machinery ‘on’ and ‘off’, respectively [37,38]. Within 30 min of the addition of estrogen, co-regulators such as SRC-1, AIB1, H2A.Z, H2ac, and p300 are rapidly recruited to ERα binding sites to activate the expression of ERα target genes [24,37,38]. Furthermore, ERα can recruit histone demethylase enzymes KDM3A, KDM4B, and KDM6B to ERα targeted chromatin to assert histone modification changes [3941].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation